Valuable source for teachers From Apartheid to democracy : South Africa 1948 - 1994, Tim Nuttal, Jeanne Hoffman, Nkosi Sishi, Sam Khandlhela : book review (Historia, 2021)
Over the past years there has been a steady decline in the general historical orientation of History 1 students. Many of them have not even taken History as a matric subject and those who have often have difficulty in connecting History to their own past experiences and memories. The upshot of all this is that first year History lecturers are experiencing more and more the same problems and needs as secondary school History teachers. This includes the need for suitable core texts to prescribe for students. From Apartheid to democracy is a school text book, specifically written to meet the need created by the Contemporary History included in the Interim Syllabus and to help school pupils relate their own world of experiences to the History they learn about at school. On the tertiary level, the book functions well as a core text to provide a historical context for more specialised studies on aspects of contemporary history. It could also function as a quick reference guide to political history of the last half of the 20th century in SouthAfrica.
Keywords: connecting History; History teachers; From Apartheid to democracy; school text book; Interim Syllabus; contemporary history